Pericytes in castration-resistant prostate cancer associated with disease progression and immunotherapy response: insights from single-cell analysis - Yifeng Qiu; Yuhan Wang; Jiahe Liu; Kai Sun; Shigeo Horie; Zhitong Bing; Qi Hou (Cancer Cell International)
Abstract Background The current immunotherapeutic strategies yield limited therapeutic benefits in patients with castration-resistant prostate cancer (CRPC) due to its immunologically “cold” tumor milieu. Pericytes play a pivotal role in facilitating metastatic dissemination and modulating immune response in malignancies. Our investigation is designed to decipher the biological effects of pericytes on CRPC and their interactions with the tumor microenvironment. Methods We leveraged single-cell transcriptomics and immunofluorescence staining to ascertain the presence and spatial distribution of pericytes in prostate cancer (PCa). Subsequently, we thoroughly delineated the phenotypic and functional characteristics of the CRPC-pericytes subpopulation. The clinical and prognostic significance of CRPC-pericytes was assessed by employing several bulk RNA-seq and microarray datasets. Additionally, we examined the association between the abundance of CRPC-pericytes and immunological features in the PCa microenvironment. Furthermore, the RM-1 subcutaneous tumor model was leveraged to assess the synergistic efficacy of platelet-derived growth factor (PDGF) signaling inhibition in conjunction with immunotherapeutic interventions. Results We discerned pericytes according to their marker genes and observed the α-SMA-positive pericytes encircling the vasculature in PCa and adjacent normal tissues. In the CRPC-pericytes subpopulation, a pronounced upregulation of PDGF signaling and angiogenesis was observed, whereas antitumor immunity-related pathways were suppressed. In addition, CRPC-pericytes displayed notably enhanced interactions with endothelial cells, fibroblasts, and myeloid cells, compared to PCa-pericytes. Patients with elevated prevalence of CRPC-pericytes exhibited notably reduced recurrence-free survival and unresponsiveness to immunotherapeutic interventions. Moreover, CRPC-pericytes were positively associated with immunosuppressive properties of the TME. Notably, combinatorial application of PDGFR inhibitor and anti-PD-1 therapy elicited substantial synergistic antitumor effects in murine PCa models. Conclusion Our investigation uncovers a CRPC-pericytes subpopulation implicated in cancer progression and immunosuppression, suggesting that therapies targeting the phenotypic transition of pericytes could act synergistically with immunotherapeutic regimens to improve survival rates in CRPC.